UPAYA MENINGKATKAN PRESTASI BELAJAR MATEMATIKA DENGAN MENGGUNAKAN MEDIA PEMBELAJARAN KERTAS BERWARNA - Suyatmiati, Suyatmiati (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2018)
This research is aimedÂ  to improve mathematics students learning achievement inelementary school, especially inmixed count operation on integer materials through the application of colored paper learning media. This research was a classroom action research refferedto Kemmis and Mc Taggartâ??s design, which includes planning, acting, observing, and reflecting. The research subject were all the student of fourth A gradeÂ  in SDN Wadungsari Waru Sidoarjo inÂ  theÂ  the period of 2016/2017. Before the implementation of the action, the classical average value is 58.75. After the action is applied, the results of the test onÂ  cycle I is 75 for classical average value and the results of the test onÂ  cycle II is 84,38 with student learning completenessKeywords:colored paper media, learning achievement